Usage model-based automated testing of C++ templates. - Sayre, Kirk
The object-oriented design of software in C++ using class templates presents many advantages over non-object-oriented or non-template based software design. However, the testing of template based C++ software involves some unique issues not usually faced during the testing of non-template based software. This paper will describe these testing issues and describe a proposed solution to these issues using a usage model-based automated testing framework.
Keywords: Software; Software engineering; Testing and debugging; Testing tools (e.g., data generators, coverage testing).; Software/Program Verification; Model checking; Design; Experimentation; Measurement; Performance; Verification